A human measure: structure, meaning and operation of the 'Lu Ban' foot-rule (鲁班尺) of the Dong carpenters. Issue 3 (14th March 2014) - Smith, Kendra Schank; Smith, Albert C.; Li, Xuemei
Abstract : The Dong carpentry rule is reflective of the Dong's culture, traditions and construction methods related to human measurement. It is dimensioned by a comparable set of lucky and unlucky units instead of abstract geometries, indicating the favorable and unfavorable units that can be applied in construction. As a measurement system derived from the human body, the units celebrate more critical sections such as the head, feet or joints, relating to the proportions of the 'master craftsman's body. Thus, on a construction site, the representation of the human body acts to convey scale and measurement, and particularly, this ruler holds the human proportion for sacred and public buildings, specifically Drum Towers and 'Wind and Rain' bridges. In this paper, the measuring system will be explored to show how it is made and assists the carpenters in dimensioning their buildings. This measurement system establishes a relationship between the construction and their beliefs.